Strategi Pengelolaan Aset Daerah di Badan Pengelolaan Keuangan dan Aset Daerah (BPKAD) Kota Makassar - Muh Faisal; Muhlis Madani; Rusliadi (Universitas Muhammadiyah Makassar, 2025)
: This study aims to analyze the regional asset management strategy at the Regional Financial and Asset Management Agency (BPKAD) of Makassar City in order to improve the effectiveness, efficiency, and accountability of regional asset management. This research is motivated by various challenges faced by BPKAD, such as suboptimal asset utilization, limited proof of asset ownership, assets controlled by unauthorized parties, and limited integration between administrative data and physical asset data. This study uses a qualitative method with a case study approach. Data were obtained through interviews, observation, and documentation. Informants in this study consisted of six people who played a direct role in asset management, namely Muh. Dakhlan, Islamiyah Sondeng, Maryana Panggalo, Muh. Rahmatullah, Muhammad Tahir, and Muh. Yusuf. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that asset management at BPKAD faces strengths in the form of regulatory and infrastructure support, weaknesses in human resources and information systems, opportunities in the form of technological developments and cooperation with third parties, and threats in the form of potential asset misuse and regulatory changes. Based on the SWOT analysis, strategies that can be implemented include optimizing asset utilization through the asset management information system (SIMBAKDA), increasing human resource capacity, strengthening asset inventory and certification, and implementing the principles of transparency and accountability as well as better governance in Makassar City.